Respuesta :
Answer:
centre of circle (h,k) is (-3,-2)
Option D is Correct.
Step-by-step explanation:
The centre of circle can be found from the equation as:
[tex](x-h)^2+(y-k)^2=r^2 \ then \ (h,k) \ is \ center[/tex]
So, the steps then by Mrs Culland are:
[tex]x^2 + y^2 + 6x + 4y - 3 = 0\\x^2 + 6x + y^2 + 4y - 3 = 0\\(x^2 + 6x) + (y^2 + 4y) = 3\\(x^2 + 6x + 9) + (y^2 + 4y + 4) = 3 + 9 + 4[/tex]
The next step will be:
[tex](x + 3)^2 + (y + 2)^2 = 16[/tex]
I assume there is some calculating mistake in the given options. Instead of 42 there should be 16, according to solution shown above.
The general equation of circle is
[tex](x-h)^2+(y-k)^2=r^2 \ then \ (h,k) \ is \ center[/tex]
In our case: [tex](x + 3)^2 + (y + 2)^2 = 16[/tex]
h= -3 and k= -2, so the centre of circle (h,k) is (-3,-2)
Option D is Correct.
Answer:
D,,,, (x+3)²+(y+2)²=4², so the center is (-3, -2).
Step-by-step explanation: